2021
DOI: 10.1016/j.heliyon.2021.e06773
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Ramadan fasting on Fetuin-A level in type 2 diabetes mellitus

Abstract: Background/Aims: Ramadan fasting creates changes in lifestyle, causing biochemical alterations that affect glucose metabolism and insulin sensitivity. This study aims to assess the impact of Ramadan fasting on glycemic control and Fetuin-A, a glycoprotein that affects insulin resistance, in patients with type 2 diabetes mellitus (T2DM). Materials and methods: This was a prospective study done among 37 patients with T2DM from Internal Medicine Polyclinic in a hospital in Jakarta, Indonesia. Anthropometric data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…111,112,[114][115][116] Ramadan fasting was found to reduce Fetuin-A levels, a glycoprotein associated with insulin resistance. 117 A recent meta-analysis reported a general reduction in body weight and waist circumference and an overall improvement of metabolic profile markers such as BGLs, HbA1c and lipid levels after Ramadan fasting. 112 In a study in the United Arab Emirates in individuals with T2D not treated with insulin, fasting was not associated with any significant short-term changes in metabolic control, glucose fluctuation or time in hypoglycemia, apart from an initial increase in glucose variability, compared with the non-fasting pre-Ramadan period.…”
Section: Fasting In Young People With T2dmentioning
confidence: 98%
See 1 more Smart Citation
“…111,112,[114][115][116] Ramadan fasting was found to reduce Fetuin-A levels, a glycoprotein associated with insulin resistance. 117 A recent meta-analysis reported a general reduction in body weight and waist circumference and an overall improvement of metabolic profile markers such as BGLs, HbA1c and lipid levels after Ramadan fasting. 112 In a study in the United Arab Emirates in individuals with T2D not treated with insulin, fasting was not associated with any significant short-term changes in metabolic control, glucose fluctuation or time in hypoglycemia, apart from an initial increase in glucose variability, compared with the non-fasting pre-Ramadan period.…”
Section: Fasting In Young People With T2dmentioning
confidence: 98%
“…Previous studies suggested that Ramadan fasting may affect metabolic profile by decreasing the frequency and amount of calorie intake, decreased physical activity, fluid restriction and changes in sleep pattern 111,112,114–116 . Ramadan fasting was found to reduce Fetuin‐A levels, a glycoprotein associated with insulin resistance 117 . A recent meta‐analysis reported a general reduction in body weight and waist circumference and an overall improvement of metabolic profile markers such as BGLs, HbA1c and lipid levels after Ramadan fasting 112 .…”
Section: Fasting In Young People With T2dmentioning
confidence: 99%
“…Besides that, according to Thewjitcharoen et al (2018b) and Andriani & Maria (2022), the following were the BMI categories: (a) underweight: 18.5 kg/ m 2 ; (b) normal: 18.5-22.9 kg/m 2 ; (c) pre-obese: 23-27.4 kg/m 2 ; and (d) obese: 27.5 kg/m 2 . The normalization of BMI in obese T2DM patients due to weight loss may also have a good impact on glycaemic management, which is among the goals that DM patients ought to strive towards (Harbuwono et al 2021).…”
Section: Anthropometrymentioning
confidence: 99%
“…Instead, a marginal benefit or no change in all parameters was seen. Second, Harbuwono et al 11 assessed the impact of RF on glycemic control and fetuin-A, a glycoprotein that affects insulin resistance, in patients with T2DM in a prospective study among 37 patients. Anthropometric data and HbA1c, fasting blood glucose (FBG), and fetuin-A levels were measured in three-time points: before, during, and after RF.…”
Section: Pathophysiologymentioning
confidence: 99%